Penerapan Prinsip-Prinsip Etika Bisnis Islam pada Hotel Syariah Kota Jambi (Studi pada OYO 2899 Mardilia Bandara Syariah Kota Jambi) - Siti Aysah; Ambok Pangiuk; Atar Satria Fikri (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2024)
In the current era of globalization, business development is occurring rapidly. The growth of various businesses is happening everywhere. The number of hotels currently available is increasing, both conventional and sharia, which is causing market competition to become increasingly fierce. Every consumer has a wide choice of products or services that they want to choose according to their individual wishes. Facilities and services are one of the factors that influence the quality of consideration of consumers or visitors in choosing hotel and lodging services. The aim of the research is to find out how the principles of Islamic Business Ethics are applied at Sharia Hotels in Jambi City, especially at OYO 2899 Ardilia Syariah Airport, Jambi City. The method used in this research is a data analysis method which refers to data collection techniques by means of observation, interviews and documentation. The research results show that facilities and services influence the application of Islamic business ethics principles in each Sharia Hotel.